Inhaled isopropyl alcohol vs. intravenous ondansetron for postoperative nausea following laparoscopic cholecystectomy under general anaesthesia: A comparative study - Devi Sharma Regmi, Bharati; Regmi, Subi; Prasad Deo, Gopendra; Paudel, Raunak (Journal of Chitwan Medical College, 2025)
Introduction: Postoperative nausea (PON) and vomiting remain common and distressing problems, affecting up to 30% of surgical patients globally. While intravenous ondansetron is a widely used antiemetic, inhaled isopropyl alcohol offers a rapid, low-cost alternative. This study compared the effectiveness of inhaled isopropyl alcohol versus intravenous ondansetron for PON. Method: After ethical approval, this prospective, randomised comparative study included ASA I–II adults (18–50 years) undergoing elective laparoscopic cholecystectomy under general anaesthesia during Mar 2024–Mar 2025 at Chitwan Medical College, Nepal. Patients developing PON in the post-anaesthesia care unit were randomised to receive either inhaled isopropyl alcohol (Gr-IPA) or 4 mg intravenous ondansetron (Gr-O). Nausea severity was measured using a verbal numeric rating scale (VNRS) at baseline and at 5-minute intervals for 30 minutes. Data were checked for normality, and analysed using IBM SPSS v-20 (independent t-test/Mann-Whitney U for numerical data; Chi-square/Fisher exact for categorical data). A p<0.05 was considered significant. Result: Of 94 enrolled patients, 91 completed the study. Mean age was 34.86±9.00 years in Gr-IPA and 36.89±8.27 years in Gr-O (p>0.05). In Gr-IPA, 24(54.5%) were females; in Gr-O, 29(61.7%) females (p>0.05). Gr-IPA showed significantly lower median VNRS scores at 5 and 10 minutes (p<0.001), indicating faster relief. From 20 minutes onward, Gr-O demonstrated more sustained nausea reduction (p<0.001). Conclusion: Our findings suggest that inhaled isopropyl alcohol may serve as a rapid, simple, and cost-effective alternative to intravenous ondansetron for initial management of post-operative nausea.